2010
DOI: 10.1111/j.1365-3180.2010.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Population growth rate of Setaria viridis in the absence of herbicide: resulting yield loss in foxtail millet Setaria italica

Abstract: Setaria viridis (green foxtail) is a common weed and is the putative ancestor of foxtail millet (Setaria italica). Population densities of S. viridis and its effect on foxtail millet yield were studied for 4 years in two locations, with three cultivars, under monoculture and no use of selective herbicide. Each year the density of S. viridis plants increased in all fields at a population growth rate k = 1.13. The stability of the k estimate in monoculture could serve as a reference value to predict the fate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is a fitness cost similar to that found for atrazine resistance in the same crop (Darmency and Pernès, 1989). We recently reported that trifluralin-and atrazine-resistant lines had similar yields in multisite experiments in China (Wang et al, 2010b), which is consistent with a comparable reproduction cost. In all, 20% is considered to be a significant yield penalty.…”
Section: Discussionsupporting
confidence: 69%
“…It is a fitness cost similar to that found for atrazine resistance in the same crop (Darmency and Pernès, 1989). We recently reported that trifluralin-and atrazine-resistant lines had similar yields in multisite experiments in China (Wang et al, 2010b), which is consistent with a comparable reproduction cost. In all, 20% is considered to be a significant yield penalty.…”
Section: Discussionsupporting
confidence: 69%
“…Variable results were observed in two other studies, but using non-isogenic materials and without knowledge of the ACCase resistance mechanism (Gill et al, 1996;Recasens et al, 2007). In addition, traits such as seed viability and longevity that were not measured in our experiment but are pertinent to the whole life cycle, have the potential to account for the observed lack of fitness difference between the S and R plants under field plots without (Wang et al, 2010). For instance, the earlier flowering and seed set of R plants could expose R seeds to longer periods of predation than S seeds.…”
Section: Discussionmentioning
confidence: 45%
“…The relationship between weeding interval to Setaria density was exponential and weeding interval to grain yield was polynomial. While, yield increment was directly proportional to time duration period of weed free plots (Wang et al, 2010).…”
Section: Water Use Efficiency and Correlation Matrixmentioning
confidence: 92%
“…Chauhan & Johnson (2010) recorded a grain yield loss of 24% for weed competition of 28 DAS and season long competition forced the maximum yield loss of 89% in rice. The period (07-35 DAS) coincide with tillering and canopy cover, thus maximum number of productive tiller loss is reported during this period that ultimately leads to lower yield (Yaduraju & Mishra, 2004). The relationship between weeding interval to Setaria density was exponential and weeding interval to grain yield was polynomial.…”
Section: Water Use Efficiency and Correlation Matrixmentioning
confidence: 99%